Statistical characterization of genetic association - Weir, Bruce (Henry Stewart Talks, 2004)
Alternative methods of estimating and testing hypotheses, Causes and description of departures from independence of alleles at one, two or three loci, Effects of multiple alleles, Comparison of allelic and genotypic association tests in the case-control setting, Trend tests
Archived at 2021/02/25